Dilemma-Based EDIH Ecosystem’s : Insights Into Innovation Leadership - Ihamäki, Pirita; Kuoppakangas, Päivikki; Kaivo-oja, Jari (United States, 2026)
Decision-making in complex innovation ecosystems, such as European Digital Innovation Hubs (EDIHs), involves navigating strategic and ethical dilemmas that challenge conventional leadership models. Despite EDIHs’ growing role in Europe’s digital transformation, limited research explores how leaders manage conflicting priorities in these multi-stakeholder environments. This study examines how dilemma-based decision-making shapes innovation leadership and dynamic capabilities in EDIHs.Grounded in Hampden-Turner’s (1990) dilemma theory and Teece’s (1997, 2007) dynamic capabilities framework, the study employed a qualitative survey with 20 responses. The survey assessed leadership models, adaptability, resilience, and strategic decision-making. Findings reveal that leaders frequently face tensions—such as balancing financial sustainability with ethical neutrality, or short-term KPIs with long-term ecosystem impact. Their ability to reconcile these dilemmas is vital for fostering innovation, trust, and resilience. Leadership in digital innovation ecosystems demands agility, foresight, and integrity (Gorelova et al., 2024; Tigre et al., 2025). Leaders must possess creativity, innovation, and an entrepreneurial mindset to guide dynamic ecosystems effectively (Taylor et al., 2025; Ercantan et al., 2024). Ethical dilemmas, as defined by Fernando (2009), involve choices between alternatives that affect both stakeholders and organizational competitiveness. In EDIHs, these dilemmas are amplified by the need to balance public trust, technological neutrality, and commercial viability. Leaders’ decisions are shaped by values, cultural context, and their ability to interpret dynamic environments, aligning with ethical leadership and moral sensitivity in complex systems (Arar & Saiti, 2022).The European Digital Innovation Hubs network, launched in 2023, supports SMEs and public sector organizations in adopting advanced digital technologies. Covering nearly 90% of European regions (168 EDIHs), the network offers services in AI, cybersecurity, and high-performance computing. By September 2024, over 200,000 participants had engaged in more than 5,000 events, through which over 18,000 services were delivered. The Digital Maturity Assessment Tool (DMAT) shows that companies follow a structured path toward digitalization, with strategy and human-centric approaches becoming increasingly important at higher maturity levels. After receiving support from EDIHs, 90% of companies improved their digital maturity scores (Carpentier et al., 2025).This study contributes to bridging leadership theory, innovation management, digital ecosystems, and entrepreneurship research. It addresses a critical gap in understanding how leaders in digital ecosystems navigate dilemmas and leverage dynamic capabilities to foster innovation, trust, and transformation. Hampden-Turner’s (1990) dilemma reconciliation model emphasizes integrating opposing perspectives rather than seeking compromises. This approach enables leaders to transform conflicting values into creative solutions that support both value creation and long-term sustainability. The findings suggest that dilemma-based decision-making is not a barrier but a catalyst for innovation leadership. Leaders who can reconcile tensions—between innovation and regulation, neutrality and commercial interest, or short-term metrics and long-term vision—are better equipped to build resilient ecosystems. These insights are particularly relevant for policymakers, ecosystem designers, and innovation leaders aiming to strengthen the role of EDIHs in Europe’s digital future.ReferencesArar, K., & Saiti, A. (2022). Ethical leadership in complex systems. Journal of Educational Administration, 60(3), 345–360.Carpentier, A., et al. (2025). Digital Maturity Assessment Tool: Impact of EDIHs on SME transformation. European Commission Report.Ercantan, A., et al. (2024). Entrepreneurial mindset in digital ecosystems. Technology Innovation Journal, 18(2), 112–129.Fernando, M. (2009). Ethical decision-making in organizations. Journal of Business Ethics, 90(3), 371–383.Gorelova, L., et al. (2024). Leadership agility in digital transformation. European Management Review, 21(1), 55–72.Hampden-Turner, C. (1990). Charting the Corporate Mind: From Dilemma to Strategy. Blackwell.Msila, V. (2024). Janusian thinking in leadership. Leadership and Change Quarterly, 12(1), 88–101.Taylor, R., et al. (2025). Innovation leadership in European ecosystems. Innovation & Strategy Review, 33(4), 205–223.Teece, D. J. (1997). Dynamic capabilities and strategic management. Strategic Management Journal, 18(7), 509–533.Teece, D. J. (2007). Explicating dynamic capabilities. Strategic Management Journal, 28(13), 1319– 1350.Tigre, P., et al. (2025). Multi-stakeholder collaboration in digital hubs. Digital Policy Studies, 9(2), 144–160.
Keywords: Decision-Making Process, Innovaiton Leadership, Dilemma, Dynamic capability
Artificial Intelligence and Social Computing 2025 : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA, 26-30 July 2025